How explanation guides belief change. Issue 10 (October 2021) - Douven, Igor
Abstract : Philosophers have argued that people ought to change their graded beliefs via Bayes' rule. Recent work in psychology indicates that people sometimes violate that rule by attending to explanatory factors. Results from computational modeling suggest that such violations may actually be rational.